OPTIMALISASI PRODUKSI KOPI INDUSTRI RUMAHAN CAP X, KOTA TANGERANG (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2022)
Optimization of Home Industry Coffee Production Cap X, Tangerang City. Kopi Cap X home industry is a home industry that processes a coffee commodity. In a daily process, the home industry has many obstacles in its production activities to optimize the resources of the home industry so that the profit, which is generated from the production, is not maximized. The problems of the resources were the raw materials, number of labours, number of machines, and operating costs. To analyze this problem, a Simplex Method of Linear Programming was applied. The result of the optimization level was Rp34.440.000 producing 200 units of arabica coffee, 450 units of robusta coffee, and 746 unit of special coffee. It was surplus Rp 1.440.000,- from the factual production.